Espectro de ação do fago Pseudomonas aeruginosa Phage UPF_PaBP1 frente a isolados clínicos e ambientais de Pseudomonas aeruginosa (host rage) e em cerúmen de ouvido artificial - Nascimento, Caroline Antunes do (2025)
Infections caused by Pseudomonas aeruginosa represent a significant therapeutic challenge in both human and veterinary medicine, primarily due to the bacterium's resistance to commonly used antimicrobials. This resistance hinders the treatment of infections such as otitis in dogs, where P. aeruginosa is frequently isolated. In this context, bacteriophages - viruses that infect and lyse bacteria - have been explored as a promising alternative therapy. This study aimed to evaluate the lytic activity and host range of a virulent bacteriophage, Pseudomonas aeruginosa Phage UPF_PaBP1, against clinical and environmental P. aeruginosa isolates. Additionally, its ability to reduce the bacterial load of the standard strain ATCC 27853 was assessed using an experimental artificial earwax model designed to simulate the canine ear canal environment. A total of 19 P. aeruginosa strains, isolated from various clinical and environmental sources, were analyzed. Initially, all strains underwent antimicrobial susceptibility testing to determine their resistance profiles. The absence of prophages in bacterial genomes was confirmed by spot test assays. The same assay was used to determine the host range of phage UPF_PaBP1 by evaluating its infectivity against each isolate. Finally, the phage’s ability to reduce bacterial load was tested in the artificial cerumen model contaminated with ATCC 27853, and bacterial quantification was performed by spread plate to determine colony-forming units (CFU/mL). Susceptibility testing revealed a high rate of antimicrobial resistance among isolates, with tobramycin showing the broadest spectrum of activity. No prophage-related activity was observed in any isolate. Phage UPF_PaBP1 was able to infect 79% of the tested strains. Under simulated otic infection conditions, phage treatment resulted in a reduction greater than 90% in P. aeruginosa load, while the phage titer increased 4.93-fold. The results demonstrate that UPF_PaBP1 has a broad host range and strong lytic activity, in addition to significant effectiveness in reducing bacterial burden in an environment that mimics otic infections. These findings support the potential of UPF_PaBP1 as a viable biocontrol agent, with promising prospects for phage therapy applications, particularly in the treatment of P. aeruginosa-induced otitis.